Iraq and Rockffler Institution for Charity 1929 – 1944 (Journal of the College of Education for Women, 2019)
The thirties and the early forties and the at end of the World War II of the last centurywitnessed several attempts carried out by the Public Health Directorate and by the IraqiMinistry of Foreign Affairs to persuade the Rockefeller Foundation to fund Iraq with itshealth program which is carried out in several regions in the world to promote the health andsocial situations since Iraq during that period in history was badly in need to such plans andprograms because of this lack of financial and technical possibilities necessary for theadvancement of health and social dire situation.The details of these attempts are deposited in the documents of the diplomatic mailrecords of the United States of America , and documents of the Middle East, Iraq 1925- 1944saved in the Iraqi National Library and Archive. We were able to obtain unique informationand it was a catalyst for us to fathom there where were no signs of this information here andthere.Overall, these documents are a correspondence conducted between the Iraqi Ministryof Foreign Affairs and the Rockefeller Foundation for charity by the US Office in Baghdad.The research finds out that the view that Iraq was largely hopeful to be included in theRockefeller Foundation for charity programs for the advancement of its own healthdeteriorated situation , and it seems that the global economic crisis that hit the United Statesof America in the thirties of the last century had the impact on the Rockefeller Foundation forcharity and its preoccupation with the activities of supporting the US military in the years ofWorld war II , as well as a the engagement of the foundation with the implementation of theFoundation charitable projects in various regions of the world has hampered the inclusion ofIraq to their programs in the health field operations.